Complete Genome Sequence of a Genotype G23P[37] Pheasant Rotavirus Strain Identified in Hungary - Gál, János; Marton, Szilvia; Ihász, Katalin; Papp, Hajnalka; Jakab, Ferenc; Malik, Yashpal S.; Bányai, Krisztián; Farkas, Szilvia L. (Genome announcements (Washington, DC), 2016)
We investigated the genomic properties of a rotavirus A strain isolated from diarrheic pheasant poults in Hungary in 2015. Sequence analyses revealed a shared genomic constellation (G23-P[37]-I4-R4-C4-M4-A16-N10-T4-E4-H4) and close relationship (range of nucleotide sequence similarity: VP2, 88%; VP1 and NSP4, 98%) with another pheasant rotavirus strain isolated previously in Germany.